Numerical Study of the Effect of Notch Geometry (Standard, Elliptical, Diamond) on Excavator Bucket Tooth Strength Based on Finite Element Analysis - Sutrisna, Sutrisna; Darmayani, Bayu Purnama Marwita; Prasetiyo, Angger Bagus (P3M Politeknik Negeri Cilacap, 2026)
The use of excavators across industrial and mining sectors is critical, particularly for bucket tooth components that perform penetration and excavation. These components often undergo wear and tear due to repeated stress and abrasion. This study aims to analyze the influence of variations in bucket tooth notch types on stress, strain, deformation, and safety factors using the Finite Element Method. The variation of standard, elliptical, and diamond notch types in the Komatsu PC200 bucket tooth model was designed using Autodesk Inventor Professional 2025. The simulation results show that the elliptical notch type has a maximum stress value of 6.2893 MPa, a maximum strain of 0.000036465 ul, and a maximum deformation of 0.00266049 mm, which is better than the standard and diamond types. Meanwhile, the diamond type has the highest maximum stress of 7.8416 MPa and the lowest deformation of 0.00259299 mm. The highest safety factor was found in the elliptical type (6.91635), which indicates that this design is safer to use in heavy workload conditions. The results of this study show that the elliptical notch type design is more efficient and has the best resistance to workload, so that it can improve the service life and performance of bucket teeth. The applied load represents a static reference for comparative evaluation among geometries; therefore, the results reflect relative design performance.